Active Vision for Scene Understanding - Grotz, Markus (Karlsruhe Series on Humanoid Robotics, 2021)
Visual perception is one of the most important sources of information for both humans and robots. A particular challenge is the acquisition and interpretation of complex unstructured scenes. This work contributes to active vision for humanoid robots. A semantic model of the scene is created, which is extended by successively changing the robot's view in order to explore interaction possibilities of the scene.